149 Quantitative Performance Assessment of a Wirelessly Powered Vagus Nerve Stimulator in a Porcine Model. (April 2023) - Habibagahi, Iman; Omidbeigi, Mahmoud; Hadaya, Joseph; Lyu, Hongming; Jang, Jaeeun; Ardell, Jeff; Bari, Ausaf A.; Babakhani, Aydin
Abstract : INTRODUCTION: Electrophysiological stimulation has been widely used in the management of various disorders, including neurological and cardiac disorders. The dependence on an implantable pulse generator (IPG) increases the risk of surgical complications, patient discomfort, and need for IPG replacement surgery in stimulation methods. Wireless and batteryless stimulators offer important capabilities such reduced need for reoperation, and shorter surgical time compared to their wired counterparts. However, stable quantitative functionality assessment of wireless systems is an essential requirement for their practical usage. METHODS: In vivo studies were performed in three anesthetized male pigs. Conventional wired stimulation using bipolar electrodes and a wireless stimulator using the circular wireless receiver (ø 13 mm, 483 mg) with cuff electrodes were implanted around the right Vagus nerve of all animals. Stimulation was performed at varying frequencies (1–20 Hz), and pulse widths (0.1–1 ms) using both systems. Heart rate, left ventricle pressure, and EKG were monitored during VNS. A paired t-test was used to compare physiological responses to different VNS systems. RESULTS: A total of 84 stimulations by the wireless device and 36 stimulations by the conventional system were performed. 72% of wireless device stimulations and 75% of the conventional VNS stimulations led to significant heart rate reduction (P < 0.05, paired t-test). There was no significant difference between conventional and wireless systems when comparing physiological markers in response to different pulse widths and stimulation frequencies. CONCLUSIONS: This study quantitatively compared functionality of a novel wireless and batteryless VNS system to a conventional VNS, and can serve as a basis for future wirelessly powered implants in the field of neurosurgery to assess functionality and perform close loop stimulation using physiological markers.